Athlete's heart in prepubertal male swimmers - (:unkn) unknown (GREENWICH MEDICAL MEDIA LTD, 2006)
To determine the cardiac response to intensive endurance training during prepuberty, we studied 22 male prebubertal swimmers who had been trained for at least 3 years, with a mean of 3.91 years and a standard deviation of 1.10 years, and 8 hours per week, the mean being 10.0 hours and the standard deviation 1.7 hours. The control group consisted of 21 boys of similar age, height and weight (p is more than 0.05 for all), who were not participating regularly in sporting activities. Left ventricular dimensions and systolic function were examined with M-Mode; velocities and durations of transmittal flow were measured with pulsed wave Doppler; and tissue Doppler velocities and durations were measured with pulsed wave tissue Doppler echocardiography. We determined the regional velocities of the lateral mitral annulus in four-chamber position, the left ventricular posterolateral wall, and the midseptum in long-axis position. Interventricular septal thickness, left ventricular posterior wall thickness, left ventricular mass and relative wall thickness were increased in swimmers (p Is less than 0.05). All the tissue Doppler measurements were similar in both groups, except the septal isovolumic relaxation time. We observed that the left ventricular wall thickness had increased concentrically in prepubertal swimmers compared to controls, without a significant change in the left ventricular diastolic diameter. This finding is contrary to the previous studies on adult swimmers. Whether the structural changes observed in our study reflect the unique cardiac adaptation of the hearts of children to exercise will only be disclosed by longitudinal studies of prepubertal athletes.
Keywords: echocardiographic changes; sports; children; LEFT-VENTRICULAR STRUCTURE; DIASTOLIC FUNCTION; CARDIOVASCULAR-RESPONSES; WALL-MOTION; CHILDREN; EXERCISE; HYPERTROPHY; RUNNERS; SPORTS